Measurements of the total Radiation from Sun and Sky in India during the IGY - MANI, ANNA; CHACKO, O.; VENKITESHWARAN, S. P. (MAUSAM, 1962)
A comparative study of the solar radiation and sunshine data recorded during the IGY at four representative stations in India, viz., Delhi, calcutta, Poona and Madras, using Moll- Gorczynski solarimeters, Bellani Spherical Pyranometers and campbell. Stoke.’ sunshine recorders has been made, The seasonal and diurnal variation of total radiation from sun and sky on a horizontal surface T at all the four stations is discussed; alsoThe variation n1onth by month of the total radiation from sun, sky and ground on a spherical surface T’, and the hours of bright sunshine S, The percentage of annual radiation received in any of the seasons October-January , February-May and June -September is roughly the same de3pite the large variations during the monsoon and winter, Poona receives more radiation than the other stations throughout the year except during the monsoon when it receives the lowest. hile the ratio T/T’ varies with the sun’s elevation, the seasons and with the nature of the surroundings and is a maximum during the Summ6r and least during the winter, it is nearly constant at all the four stations and has an average value of 2. The another of Angstrom’s formula giving the empirical relationship between both radiation form sun and sky and the duration of sunshine have been determind for all the four staion for both cloudy and all days using the IGY data.